Detection and identification of acetylcholinesterase inhibitors in Annona cherimola Mill. by effect‐directed analysis using thin‐layer chromatography‐bioassay‐mass spectrometry. Issue 6 (11th June 2019) - Galarce‐Bustos, Oscar; Pavón, Jessy; Henríquez‐Aedo, Karem; Aranda, Mario
Abstract: Introduction: Acetylcholinesterase (AChE) inhibitors are considered an important strategy in the treatment of neurological disorders such as Alzheimer's disease. A simple and fast planar chromatography‐bioassay methodology has been established to detect bioactive molecules in cherimoya fruit. Objective: Detect and identify AChE inhibitors in cherimoya by high‐performance thin‐layer chromatography (HPTLC)‐bioassay‐mass spectrometry (MS) and related techniques. Methodology: Effect‐directed analysis by planar chromatography‐bioassay‐mass spectrometry was applied to detect and identify AChE inhibitors in pulp, peel and cherimoya seed. Bioassay was optimised establishing the following conditions: enzymatic solution (1.0 U mL −1 ), 1‐naphtyl acetate substrate (1.5 mg mL −1 ) and Fast Blue B salt (1.0 mg mL −1 ). TLC‐MS interface was used to directly elute the active zones into a mass spectrometer or to a micro‐vial for further off‐line studies. Results: Two AChE inhibitory bands were detected in peel extracts. An analysis via HPTLC‐MS and high‐performance liquid chromatography diode array detector tandem mass spectrometry (HPLC‐DAD‐MS/MS) allowed to characterise three potential AChE inhibitors: anonaine ( m/z 266 [M + H] + ; UV λ max = 269.6 nm), glaucine ( m/z 256 [M + H] + ; UV λ max = 282.9 and 300.6 nm) and xylopine ( m/z 296 [M + H] + ; UV λ max = 278.5 nm). Conclusions: The application of this optimised high throughput method allowed to establish the presence of three potential AChE inhibitors in cherimoya peel. For the first time AChE inhibitory capacity of these alkaloids is reported. Abstract : A fast and cost‐efficient HPTLC‐bioassay methodology for acetylcholinesterase inhibitors (AChEi) detection was established. Both, enzyme concentration and incubation time, were reduced achieving an important decrease in cost and analysis time. Application of this effect directed methodology allowed to detect and identify the presence of two potential AChEi in cherimoya (Annona cherimolaMill) peel: anonaine and glaucine, and a possible candidate, xylopine. To the best of our knowledge this activity is reported for the first time.